(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Aim: To compare the adhesion prevention and hemostatic effects of different types of nasal packing viz. medicated gauze packing, glove finger packing and merocel packing. Study Design: Prospective Study, in which 105 patients were, enrolled with effect from September 2011 to March 2012. Methods: This study was done in postgraduate department of ENT - HNS in Govt. Medical College, Srinagar. 105 patients undergoing septoplasty were randomly distributed in three groups, Group A, Group B, and Group C. Group A patients were packed postoperatively with medicated gauze packing, Group B with glove finger packing and Group C with merocel packing. Patients were then examined and regularly observed and followed for post-septoplasty hemorrhage and adhesions. Results: The average number of cotton balls used to clean the blood soakage on day one was 10 in Group A, 13 in Group B and 15 in Group C. On comparing the results of medicated gauze packing with merocel packings, the difference was not statistically significant(p<0.20), though apparently conventional anterior nasal packing (ANP) appeared to be better hemostatic than other types of packings. At 4 weeks postoperatively, the number of patients who developed adhesions were 10 (28.6%) in Group A, 8 (22.9%) in Group B and none (0 %) in Group C. On comparing the results of merocel packing with conventional ANP with highest rate of adhesion formation, the difference was statistically significant (p<0.002). Also on an average minimal number of paracetamol tablets (Dosage Strength 500 mg) were consumed by patients whose noses were packed with merocel (8 tablets) as compared to conventional ANP (13 tablets) and glove finger (8 tablets) over a period of one week. Conclusions: Hemostatic effects were best observed with medicated gauze packing, though the difference was not statistically significant. Adhesion formation which is one of the most important determinants of success of septoplasty is best prevented by merocel packing. If good expertise is observed during septoplasty with proper sterilization technique, postseptoplasty hemorrhage is quite uncommon and adhesion prevention becomes the single most important factor. Merocel packing should thus be carried out in almost all cases. In cases where postoperative bleeding is suspected, classical medicated gauze packing should be done. The morbidity associated with postoperative pain was minimal with merocel packing. DOI:http://dx.doi.org/10.3329/bjo.v18i2.11989 Bangladesh J Otorhinolaryngol 2012; 18(2): 129-132